2008
DOI: 10.1021/ja710520q
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Cryptophycin P450 Epoxidase Reveals Substrate Tolerance and Cooperativity

Abstract: Cryptophycins are potent anticancer agents isolated from Nostoc sp. ATCC 53789 and Nostoc sp. GSV 224. The most potent natural cryptophycin analogues retain a β-epoxide at the C2′-C3′ position of the molecule. A P450 epoxidase encoded by crpE recently identified from the cryptophycin gene cluster was shown to install this key functional group into cryptophycin-4 (Cr-4) to produce cryptophycin-2 (Cr-2) in a regio-and stereospecific manner. Here we report a detailed characterization of the CrpE epoxidase using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 66 publications
1
34
0
Order By: Relevance
“…[17] Perhaps of great significance, however, is the observation that peptidomimetic catalyst 9 exhibits conformational properties that are surprisingly different from catalyst 5. Whereas catalyst 5 appears as a single conformation in solution by 1 H NMR (400 MHz) (Figure 1 a), consistent with the b-turn observed in the X-ray structure of 8, catalyst 9 appears as a heterogeneous 3.5:1 mixture of two distinct catalyst conformations (Figure 1 b). Notably, the signals coalesce when the NMR sample is heated to 100 8C ([D 6 ]DMSO solvent).…”
supporting
confidence: 74%
See 1 more Smart Citation
“…[17] Perhaps of great significance, however, is the observation that peptidomimetic catalyst 9 exhibits conformational properties that are surprisingly different from catalyst 5. Whereas catalyst 5 appears as a single conformation in solution by 1 H NMR (400 MHz) (Figure 1 a), consistent with the b-turn observed in the X-ray structure of 8, catalyst 9 appears as a heterogeneous 3.5:1 mixture of two distinct catalyst conformations (Figure 1 b). Notably, the signals coalesce when the NMR sample is heated to 100 8C ([D 6 ]DMSO solvent).…”
supporting
confidence: 74%
“…Whereas the 1 H NMR spectra for catalyst 9 reveal a 3.5:1 conformational mixture (23 8C), fluoroalkene catalyst 11 exhibits an approximately 10:1 mixture of conformations at the same temperature (Figure 1 c). Once again, coalescence of the spectrum is observed when the sample is examined by 1 …”
mentioning
confidence: 99%
“…The same research group also reported that the thioesterase portion of the crpD synthase could be expressed in a heterologous host, purified, and then reacted in vitro to produce cryptophycin analogs from synthetic, linear precursors [29]. This chemoenzymatic approach was further improved by the identification and purification of the cryptophycin P450 epoxidase, which allowed the chemoenzymatic formation of the benzylic epoxide from styrene-containing cryptophycin precursors [30]. Ultimately, the results from these synthetic and biosynthetic studies could be used to develop a second generation of cryptophycins with improved efficacy with lower toxicity than the first clinical candidate, cryptophycin 52.…”
Section: Cytotoxic Metabolites From Cyanobacteriamentioning
confidence: 99%
“…Cooperativity of cytochromes P450 has been documented in vivo (Tang & Stearns, 2001), in liver microsomes (Oda & Kharasch, 2001; Zhang et al, 2004; Di Marco et al, 2005; Niwa, Murayama, & Yamazaki, 2008a) and in reconstituted systems with purified and isolated individual enzymes, as reviewed in (Guengerich, 1999; Houston & Kenworthy, 2000; Guengerich, 2005; Houston & Galetin, 2005; Atkins, 2006; Tracy, 2006) (Hlavica & Lewis, 2001) (Davydov & Halpert, 2008). In addition to the textbook examples of cooperative cytochromes P450 such as CYP107, CYP3A4, and CYP2C9, cooperativity has also been reported for mammalian xenobiotic metabolizing enzymes CYP1A2 (Sohl et al, 2008), CYP2A6 (Harrelson, Atkins, & Nelson, 2008), CYP2B1 (Scott, He, & Halpert, 2002), CYP2B6, and CYP2E1 (Spatzenegger et al, 2003), for bacterial enzymes CYP102 (Gustafsson et al, 2004; van Vugt-Lussenburg et al, 2006), CYP130 (Ouellet, Podust, & Ortiz de Montellano, 2008), CYP158A2 (Zhao et al, 2005), P450 crpE (Ding et al, 2008), and even for chloroperoxidase (Torres & Aburto, 2005; Aburto, Correa-Basurto, & Torres, 2008). …”
Section: Introductionmentioning
confidence: 95%